Determinant factors in purchasing premium vehicles: An analysis based on the Theory of Planned Behavior - Lima, Italo Pantaleão; Faustino-Dias, Álvaro Freitas (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: Premium vehicles’ purchase peculiarities are, often, characterized due varied factors about functionality, including symbolism of status, prestige and social differentiation. To investigate these aspects, the current research was based on Ajzen's (1991) Theory of Planned Behavior (TPB), which identifies three central constructs: attitude toward the behavior, subjective norms, and perceived behavioral control. Purpose: The aim was to understand the determinant factors of purchasing luxury vehicles, based on TPB constructs. Method: Data collection was developed through semi-structured interviews with premium vehicle consumers. The interviews were qualitatively analyzed using content analysis technique, through QDA Miner software, to identify central themes according TPB constructs. Results: This research evidenced that attitudes toward behaviors are largely positive, influenced by social status and emotional benefits such as the sense of personal achievement. Subjective rules varied, being more relevant for professionals in contexts where public image is valued. Perceived behavioral control was mainly influenced by financial conditions and opportunities. Factors such as vehicle comfort and safety also contributed to strengthening the purchase intention. Conclusions: In the context of luxury vehicle purchases, consumers are strongly influenced by self-image and social prestige, while financial control plays a relevant role in purchase intention.